(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Lesions of the sinonasal/intranasal region are commonly encountered in clinical practice and important from clinical and pathological perspectives as they have varieties of histological patterns. Despite its importance for an accurate diagnosis, histology differences among intranasal polyps and its clinical implications are rarely reported in the literature. Objective: To determine the Morphological spectrum of intranasal polyps by histopathology in patients presenting in a tertiary care hospital. Study Design: Descriptive cross sectional study. Setting: Department of pathology Fatima Jinnah Medical College, Lahore. Duration: Six months from 18-08-2012 till 18-02-2013. Methods: 85 patients of all ages and both gender having intranasal polyp presented to the OPD & indoor of ENT department of Sir Ganga Ram Hospital, Lahore were included in the study. All the tissues were fixed in 10% buffered formalin, processed, stained with H & E and studied by the consultant for various histopathological patterns in the department of pathology Fatima Jinnah Medical College, Lahore. Demographic features and consent of the patients were noted. Results: Out of 85 polyp samples, 49 (57.6%) had fibroinflammatory pattern, 25 (29.4%) had edematous/eosinophilic polyp, 8 (9.4%) had inverted papilloma, 2 (2.4%) had hemangioma, 1 (1.2%) had angiofibroma. Out of 85 cases, there were 74 cases (87.1%) with different types of non-neoplastic lesions among which inflammatory polyp (49 cases, 66.2%) was the commonest lesion observed in this region. Conclusions: Categorizing the intranasal polyps according to histopathological features into varioustypes, helps us to determine the treatment modalities, clinical outcome and prognosis of the disease, so all intranasal polyp needs histological examination. Inflammatory pattern prevailed in the population studied